New Times revisited: Britain in the 1980s. Issue 2 (3rd April 2017) - Hilton, Matthew; Moores, Chris; Sutcliffe-Braithwaite, Florence
Abstract: The authors in this volume are collectively engaged with a historical puzzle: What happens if we examine the decade once we step out of the shadows cast by Thatcher? That is, does the decade of the 1980s as a significant and meaningful periodisation (equivalent to that of the 1960s) still work if Thatcher becomes but one part of the story rather than the story itself? The essays in this collection suggest that the 1980s only makes sense as a political period. They situate the 1980s within various longer term trajectories that show the events of the decade to be as much the consequence as the cause of bigger, long-term historical processes. This introduction contextualises the collection within the wider literature, before explaining the collective and individual contributions made.